A Comprehensive Review on the Recent Applications and Development in Nanocarriers (Asian Journal of Pharmaceutics (AJP), 2024)
Nanocarriers have shown promise as effective delivery vehicles. Controlled release, and enhanced efficacy oftherapeutics, imaging agents, and functional payloads in various applications. An overview of the synthesisprocesses, characterization methodologies, and uses of nanocarriers in agriculture, environmental sustainability,and healthcare is given in this abstract. Common types of nanocarriers, including liposomes, polymericnanoparticles, dendrimers, and metal-based nanoparticles, are discussed, along with their synthesis methodsand key properties. Characterization techniques such as transmission electron microscopy, dynamic lightscattering, Fourier transform infrared spectroscopy, and cell viability assays are highlighted for evaluating thephysicochemical properties, stability, and biocompatibility of nanocarriers. Applications of nanocarriers in drugdelivery, diagnostics, gene therapy, agriculture, and environmental remediation are explored, showcasing theirpotential to address critical challenges and improve human health and environmental sustainability. Despitetheir promise, nanocarriers face challenges such as biocompatibility concerns, stability issues, and regulatoryconsiderations, necessitating interdisciplinary collaboration and rigorous safety assessments for their successfultranslation into practical use. Looking ahead, nanocarriers hold tremendous promise for personalized medicine,combination therapies, smart and stimuli-responsive systems, theragnostic, and sustainable solutions, shaping afuture where precision, efficiency, and tailored solutions transform healthcare, agriculture, and environmentalmanagement. To fully utilize nanocarrier technology and advance science, health, and technology for the good ofsociety, more funding, cooperation, and research will be needed.